Desarrollo de producto cosmético natural a base de aceite esencial de té verde, extracto de albahaca y de probióticos y prebióticos generados de la fermentación de arroz a partir de Lactobacillus Plantarum (2022)
This project arises from the need to innovate in a product that is aware of the environmental impact that the cosmetic industry has at the production level and the importance of maintaining the health of facial skin, avoiding harmful chemical products and leaving conventional cosmetics behind. to encourage natural cosmetics, from different organic raw materials such as green tea essential oil, basil extract and probiotics generated from the fermentation of rice water and its prebiotics. According to the results, the efficiency of the technical parameters for a cosmetic of organic origin, according to Ecocert and Invima, is demonstrated. Therefore, 98% of the product is made from natural raw material approved by Ecocert for COSMOS certification. The product is viable at an economic level and can be distributed for sale and consumption with an estimated value of $30,000 COP, according to a projection made for the production of 200 tons / year to meet said value.